Calculation Of Coliform Number Using Most Probable Number (MPN) Methods On Soy Milk Sold in Pogot Area Of Surabaya - nisaa, racma (Journal of Stem Cell Research and Tissue Engineering, 2020)
The quality of drinks is one of the problems that exist in society, especially because of bacterial contamination of drinks that often occurs in developing countries. One of them is soy milk drinks that are contaminated by bacteria including those sold by street vendors in the Pogot area of Surabaya. Based on the background description in this study can be formulated as follows: Is the number of Most Probable Number (MPN) Coliform in soy milk sold by street vendors in the Pogot area of Surabaya fulfill the Indonesian National Standard (SNI) 7388: 2009? The purpose of this study was to determine the amount of Coliform in soy milk sold by street vendors in the Pogot area of Surabaya compared to the Indonesian National Standard (SNI) 7388: 2009 regarding the maximum limit of microbial contamination in food. This study used a descriptive study design that soy milk sold by street vendors in the Pogot area of Surabaya was the population. Samples were used as many as 16 samples from 4 street vendors, each of which was taken 4 then laboratory-tested and analyzed using percentages. Based on the requirements of the Indonesian National Standard (SNI) 7388: 2009, the limit of contamination of the Most Probable Number (MPN) Coliform in soy milk is 20 / ml. Based on the results of the research of 4 soy milk traders there were 2 traders whose the results fulfilled the requirements of the Indonesian National Standard (SNI) and 2 traders whose the results didn't  fulfill the requirements of the Indonesian National Standard (SNI). So 50% were eligible (MS) and 50% were not eligible (TMS).